A silicon-magnesium / carbonitrided silicon / hierarchical porous carbon-lithium fluoride composite negative electrode material with a self-repairing interface and a preparation method and application thereof
Patent Information
- Application Number
- CN202611092967.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]针对现有技术所存在的上述缺点,本发明提供了一种具有自修复界面的硅镁/碳氮化硅/分级多孔碳-氟化锂复合负极材料及其制备方法与应用,能够有效解决现有硅基负极材料因充放电过程中硅剧烈体积膨胀所引发的界面失效、电极结构粉化以及固体电解质界面SEI膜不稳定且反复破裂再生,从而导致活性锂和电解液不断消耗、电池首次库伦效率低、循环寿命短的问题
[0038]1、本发明通过在硅镁合金活性核表面原位碳氮化硅化学键合层,再包覆内置氟化锂纳米颗粒的多级孔隙碳骨架,解决了传统硅碳负极界面结合弱、体积剧烈膨胀及SEI膜持续消耗的问题,实现了优异的综合电化学性能:在0.5C倍率下循环1000次后容量保持率高达93.0%,电极厚度膨胀率低至35%,首次充电比容量达2646 mAh/g,首次库伦效率高达96.2%,且兼具优异的倍率性能(5C/0.2C容量比92%),大幅提升了硅基负极材料的实际商业化应用潜力;
Smart Images

Figure CN122991978A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, specifically to a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface, its preparation method, and its application. Background Technology
[0002] Developing lithium-ion batteries with higher energy density is crucial for advancing electric vehicles, portable electronic devices, and large-scale energy storage technologies. The theoretical specific capacity of currently commercially available graphite anode materials (372 mAh / g) is nearing its physical limit, restricting further improvements in battery energy density. Silicon (Si), due to its extremely high theoretical specific capacity (approximately 4200 mAh / g), suitable delithiation potential, and abundant reserves, is considered the most promising next-generation anode material. However, during charging and discharging, silicon undergoes alloying / dealloying reactions with lithium, resulting in volume expansion and contraction exceeding 300%. This drastic volume change directly leads to the rupture and pulverization of active material particles, damaging the electrode conductive network. Simultaneously, its fragile solid electrolyte interphase (SEI) film repeatedly ruptures and regenerates, irreversibly consuming electrolyte and active lithium, resulting in low coulombic efficiency, rapid capacity decay, and short cycle life. Furthermore, the dramatic changes in electrode thickness also pose significant challenges to battery mechanical safety and structural design. Therefore, how to effectively suppress or adapt to the volume effect of silicon is the core scientific problem and technological bottleneck for its commercial application.
[0003] To address these challenges, existing technologies have developed various strategies, such as material nanosizing to reduce absolute strain, compositing with carbon materials to utilize carbon's conductivity and buffering capacity, designing yolk-shell or porous carbon frameworks to reserve space for volume expansion, introducing metals to form silicon alloys to utilize plastic stress dispersion, and enhancing stability through interface engineering. Among these, using porous carbon frameworks loaded with nano-silicon as the core, and improving performance through structural design and surface modification, is currently the mainstream technical approach. For example, Chinese patent application CN118825269A designed a resin-based composite porous carbon framework to regulate pore size distribution and buffer expansion; CN118919673A designed a nanodiamond-reinforced porous carbon framework to improve mechanical strength and conductivity; CN118978160A constructed a multi-level conductive network with carbon nanotubes / carbon / conductive polymers multilayer coating; CN118929633A optimized stress distribution using a multi-level structure of alternating silicon / carbon deposition; and CN118825278A improved the stability of the electrode-electrolyte interface through a polysiloxane shell. These approaches share the common goal of improving the cycling stability of silicon-carbon composites by combining a porous carbon framework with one or more surface modifications / coatings.
[0004] However, the aforementioned mainstream technologies still have common limitations and obvious drawbacks in practical applications: First, the interfacial bonding is not long-lasting. In existing solutions, the interaction between silicon and the carbon framework or coating layer mainly relies on physical adsorption or weak chemical interaction. Under the huge stress of long-term cycling, interfacial slippage and separation are prone to occur, leading to the failure of the conductive network. Second, the dynamic adaptability of the buffer structure is limited. Existing technologies mostly rely on pre-designed static pores or coating layers, which are difficult to adapt to the non-uniform and dynamic volume expansion of silicon during cycling in real time, which easily leads to local stress concentration and structural pulverization. Finally, there is a lack of active stabilization mechanism for the SEI film. Existing solutions focus on physical isolation and do not pay enough attention to how to actively promote the formation of a stable, dense, and self-healing SEI film, resulting in an unstable SEI film that continuously consumes active lithium and electrolyte.
[0005] Therefore, the aforementioned technical problems urgently need to be solved. Summary of the Invention
[0006] To address the aforementioned shortcomings of existing technologies, this invention provides a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface, its preparation method, and its application. This material effectively solves the problems of interface failure, electrode structure pulverization, and unstable and repeatedly ruptured SEI film at the solid electrolyte interface caused by the drastic volume expansion of silicon during charging and discharging in existing silicon-based anode materials. These problems lead to continuous consumption of active lithium and electrolyte, low initial coulombic efficiency, and short cycle life.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface, the method comprising:
[0009] (1) Prepare silicon-magnesium alloy active cores from silicon powder and magnesium powder;
[0010] (2) Preparation of hierarchical porous carbon framework;
[0011] (3) Lithium fluoride nanoparticles are embedded in the voids of the hierarchical porous carbon framework to form a hierarchical porous carbon framework carrying lithium fluoride nanoparticles.
[0012] (4) The silicon-magnesium alloy active core is mechanically mixed with the hierarchical porous carbon framework loaded with lithium fluoride nanoparticles to form a composite precursor.
[0013] (5) Chemical vapor deposition is performed on the composite precursor to grow a silicon carbonitride interface layer in situ on the surface of the silicon-magnesium alloy active core, thereby forming the composite anode material.
[0014] Furthermore, in step (1), the preparation of silicon powder and magnesium powder into a silicon-magnesium alloy active core includes:
[0015] Weigh silicon powder and magnesium powder according to the target atomic ratio, and ball mill the silicon powder and magnesium powder under an argon protective atmosphere. The ball-to-material ratio is (10:1) to (30:1) to obtain silicon-magnesium mixed powder.
[0016] The silicon-magnesium mixed powder is then subjected to heat treatment at 450-600℃ for 1-4 hours to obtain the active core of the silicon-magnesium alloy.
[0017] Furthermore, the target atomic ratio is (6:4) to (9:1), preferably (6:4) to (8:2), and more preferably 7:3.
[0018] Furthermore, in step (2), the preparation of the hierarchical porous carbon framework includes:
[0019] Silica nanospheres, polymethyl methacrylate microspheres and polystyrene microspheres were mixed in a mass ratio of 1:2:1 and dispersed in ethanol to form a uniform template suspension.
[0020] The template suspension was mixed with the carbon precursor solution and stirred to obtain a carbon precursor-template composite suspension.
[0021] The carbon precursor-template composite suspension was pre-cured by evaporating solvent at 80°C, and then heated to 700-900°C under argon atmosphere for heat preservation carbonization to obtain the carbonized block.
[0022] The carbonized block is immersed in hydrofluoric acid solution to remove silica, and then Soxhlet extraction is performed to remove polymethyl methacrylate and polystyrene to obtain the hierarchical porous carbon skeleton.
[0023] Furthermore, the volume ratio of the template suspension to the carbon precursor solution is (1:2) to (2:1).
[0024] The carbon precursor solution is an ethanol solution of phenolic resin, with a phenolic resin mass fraction of 10-30 wt%.
[0025] Further, in step (3), the embedding of lithium fluoride nanoparticles into the voids of the hierarchical porous carbon framework to form a hierarchical porous carbon framework carrying lithium fluoride nanoparticles includes:
[0026] The hierarchical porous carbon framework is immersed in an ethanol solution of lithium nitrate and ammonium fluoride for ultrasonic impregnation, then vacuum dried, and then heat-treated in an argon atmosphere at a temperature of 200~400℃ to generate lithium fluoride nanoparticles, which are then embedded in the pores of the carbon framework to obtain the hierarchical porous carbon framework carrying lithium fluoride nanoparticles.
[0027] Furthermore, the concentrations of lithium nitrate and ammonium fluoride are both 0.05-0.5 mol / L, and the heat treatment temperature is 200-400℃.
[0028] Further, in step (5), the chemical vapor deposition of the composite precursor to grow a silicon carbonitride interface layer in situ on the surface of the silicon-magnesium alloy active core, ultimately forming the composite anode material, includes:
[0029] Under an argon protective atmosphere, the composite precursor is heated to 850~950℃, and then a mixture of methane and ammonia is introduced to react, thereby growing a silicon carbonitride interface layer in situ on the surface of the silicon-magnesium alloy active core.
[0030] After the reaction is complete, the methane and ammonia gas are turned off, and the mixture is allowed to cool naturally under an argon protective atmosphere to obtain the composite anode material.
[0031] Furthermore, in step (5), the volume ratio of methane to ammonia is 1:5 to 1:1.
[0032] Secondly, the present invention also provides a silicon-magnesium / silicon carbonitride / hierarchical porous carbon-fluoride composite anode material with a self-healing interface, the composite anode material comprising: a silicon-magnesium alloy active core, a silicon carbonitride interface layer coated on the surface of the silicon-magnesium alloy active core, a hierarchical porous carbon framework coated outside the interface layer, and lithium fluoride nanoparticles uniformly dispersed in the hierarchical porous carbon framework.
[0033] Furthermore, in the silicon-magnesium alloy active core, the atomic ratio of Si:Mg is (6:4) to (9:1), preferably (6:4) to (8:2), and more preferably 7:3.
[0034] Furthermore, the thickness of the silicon carbonitride interface layer is 5-50 nm;
[0035] The hierarchical porous carbon framework has a hierarchical pore structure of mesopores, macropores and macropores. The mesopores have a diameter of 2-20 nm, the macropores have a diameter of 50-300 nm, and the macropores have a diameter of 0.5-5 μm.
[0036] Furthermore, the mass of the lithium fluoride nanoparticles accounts for 1%-5% of the total mass of the composite anode material.
[0037] The technical solution provided by this invention has the following advantages compared with the known prior art:
[0038] 1. This invention solves the problems of weak interfacial bonding, drastic volume expansion, and continuous SEI film consumption in traditional silicon-carbon anodes by coating a silicon-magnesium alloy active core with an in-situ silicon carbonitride chemical bonding layer and then encapsulating it with a multi-level porous carbon framework containing lithium fluoride nanoparticles. This results in excellent comprehensive electrochemical performance: after 1000 cycles at 0.5C, the capacity retention rate is as high as 93.0%, the electrode thickness expansion rate is as low as 35%, the first charge specific capacity reaches 2646 mAh / g, the first coulombic efficiency is as high as 96.2%, and it also has excellent rate performance (5C / 0.2C capacity ratio of 92%), which greatly enhances the practical commercial application potential of silicon-based anode materials.
[0039] 2. This invention employs a micron-sized silicon-magnesium alloy as the active core. The addition of magnesium forms a plastic metallic phase. The plastic deformation of the magnesium metallic phase during charging and discharging directly absorbs and dissipates the micro-stress generated by the expansion of the silicon phase, thereby improving the fracture resistance of the active material. Externally, it is complemented by a hierarchical porous carbon framework with clearly defined functions: mesopores (2-20 nm) ensure rapid ion diffusion, macropores (50-300 nm) directionally accommodate volume expansion, and macropores (0.5-3 μm) provide a stable mechanical framework. The silicon-magnesium alloy active core dissipates stress from within the material, while the hierarchical porous carbon framework provides hierarchical buffer space from the outside. The synergy of both significantly reduces the overall thickness expansion rate of the electrode.
[0040] 3. This invention introduces a silicon carbonitride interface layer and, with the help of a simplified one-step chemical vapor deposition (CVD) process, simultaneously achieves densification and strengthening of the carbon skeleton at a high temperature of 850-950℃. Strong covalent bonds such as Si-C and Si-N are formed between the silicon carbonitride interface layer and the core silicon and the outer carbon skeleton, establishing a strong chemical connection that exceeds physical adsorption, ensuring the reliability of the electron transport channel in long-term cycling.
[0041] 4. This invention pre-embeds lithium fluoride (LiF) nanoparticles into the pores of a carbon framework. During long-term battery cycling, when the fragile SEI film is damaged due to volume changes, these embedded LiF particles can preferentially undergo dissolution and redeposition reactions at the defect sites, thereby achieving dynamic in-situ repair of interface film defects and promoting the formation and maintenance of a stable interface film. Attached Figure Description
[0042] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0043] Figure 1 This is a flowchart illustrating the preparation technology of the composite negative electrode material sample of the present invention.
[0044] Figure 2 The graph shows the long-cycle stability test results of the battery using the composite anode material sample of the present invention as the anode at a rate of 0.5C.
[0045] Figure 3 This is a first charge-discharge curve of a battery using the composite negative electrode material sample of the present invention as the negative electrode. Detailed Implementation
[0046] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.
[0047] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail. The terms “comprising,” “including,” “having,” “containing,” etc., as used herein are open-ended terms, meaning that they include but are not limited to. Unless the context clearly indicates otherwise, the expressions “a” and “an” as used herein include plural references. It should be noted that “first,” “second,” etc., are used merely for convenience of description and distinction and should not be construed as indicating or implying relative importance. The term “about” as used herein indicates a range of ±20% of the following numerical value. In some embodiments, the term “about” indicates a range of ±10% of the following numerical value. In some embodiments, the term “about” indicates a range of ±5% of the following numerical value. The invention is further described below with reference to embodiments.
[0048] Example: Refer to Figures 1 to 3 .
[0049] To address the problems of interfacial failure, structural pulverization, and continuous SEI film growth caused by the volume expansion of silicon in existing silicon-carbon composite anode materials, this invention proposes a method using a silicon-magnesium alloy (Si... x Mg y The integrated composite structure is centered on "active core—in-situ grown silicon carbonitride chemically bonded interface layer—hierarchical porous carbon framework—built-in lithium fluoride (LiF) repair agent nanoparticles". Firstly, magnesium is introduced to form a plastic Si... x Mg y An alloy core is used to intrinsically disperse stress. Then, a silicon carbonitride interface layer with strong covalent bonds to both the core and outer carbon framework is constructed in situ on the alloy core surface via chemical vapor deposition, ensuring a robust connection. Finally, LiF nanoparticles are pre-uniformly embedded in a hierarchical porous carbon framework with mesopores (2-10 nm), macropores (50-200 nm), and macropores (1-3 μm), enabling dynamic repair of the damaged SEI film during cycling and forming a stable LiF-rich interface. This invention achieves synergistic optimization of active materials, buffer framework, and interface chemistry. After 1000 cycles at 0.5C, the capacity retention is 93.0%, the 5C / 0.2C rate capacity ratio is 92%, the electrode thickness expansion rate is 35%, the initial charge specific capacity is 2646 mAh / g, and the initial coulombic efficiency is improved to 96.2%.
[0050] A self-healing silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material and its preparation method are described below. Figure 1 As shown, the details are as follows:
[0051] (a) Silicon-magnesium alloys (Si x Mg y Preparation of active cores
[0052] 1. Raw material preparation: Weigh high-purity silicon powder (99.9%, particle size ~100 nm) and magnesium powder (99.9%, particle size ~50 μm) according to the target atomic ratio (e.g., Si:Mg = 7:3).
[0053] 2. Mechanical alloying: The raw material is placed in the stainless steel tank of a high-energy planetary ball mill and ball-milled for 10 to 30 hours at a speed of 250 to 350 rpm under an argon protective atmosphere, with a ball-to-material ratio of 10:1 to 30:1.
[0054] 3. Heat treatment: The ball-milled powder is heat-treated in a tube furnace at 450~600℃ for 1-4 hours under an argon atmosphere to promote alloying and release internal stress.
[0055] 4. Sieving: The obtained alloy powder is sieved using a 400-mesh sieve to obtain Si with uniform particle size distribution. x Mgy Alloy core precursor;
[0056] (II) Preparation of hierarchical porous carbon framework and embedding of LiF nanoparticles
[0057] 5. Template preparation: Silica nanospheres (2-20 nm), polymethyl methacrylate (PMMA) microspheres (30-300 nm) and polystyrene (PS) microspheres (0.5-5 μm) are mixed at a mass ratio of 1:2:1, dispersed in ethanol, and ultrasonically formed into a uniform template suspension;
[0058] 6. Carbon precursor impregnation: Mix the above template suspension with phenolic resin ethanol solution (concentration 10-30 wt%) at a volume ratio of 1:2-2:1 and stir for 8-14 hours to allow the phenolic resin to fully fill the template gaps, thus obtaining a carbon precursor-template composite suspension.
[0059] 7. Pre-curing and carbonization: Evaporate the solvent and pre-cur the carbon precursor-template composite suspension at 80°C, and then carbonize it in a tube furnace under an argon atmosphere by heating to 700-900°C at a rate of 2-10°C / min and holding for 1-3 hours.
[0060] 8. Template removal and pore formation: The carbonized bulk material is immersed in 10% hydrofluoric acid (HF) solution for 24 hours to remove the SiO2 template, and then extracted with toluene Soxhlet for 48 hours to remove PMMA and PS templates, resulting in a hierarchical porous carbon framework with mesopores, macropores and macropores.
[0061] 9. Introduction of LiF nanoparticles: A hierarchical porous carbon framework is immersed in a mixed ethanol solution of lithium nitrate (LiNO3) and ammonium fluoride (NH4F) (both concentrations 0.05-0.5 mol / L) and ultrasonically assisted for 2 hours. Subsequently, it is dried in a vacuum oven at 60℃, and then heat-treated at 200-400℃ for 0.5-2 hours under an argon atmosphere, allowing LiNO3 to react with NH4F to generate LiF nanoparticles, which are then embedded in situ into the pores of the carbon framework.
[0062] (III) Construction of composite structure and in-situ growth of silicon carbonitride interface layer
[0063] 10. Preparation of composite precursor: The Si obtained in step one... x Mg y The alloy core and the hierarchical porous carbon framework powder loaded with LiF obtained in step two are mechanically mixed at a mass ratio of 1:2-1:5 (active material: carbon framework);
[0064] 11. Chemical Vapor Deposition (CVD) Growth of the Interface Layer: The mixed powder is spread evenly in a quartz boat and placed in the isothermal zone of a tube furnace. Under argon carrier gas, the temperature is increased to 850-950℃ at a rate of 5-15℃ / min. Then, a mixed gas of methane (CH4, carbon source) and ammonia (NH3, nitrogen source) (CH4:NH3 = 1:5-1:1, volume ratio) is introduced at a flow rate of 50-200 sccm, and the reaction is carried out for 1-4 hours. CH4 and NH3 decompose at high temperature and form a layer on Si. x Mg y The surface of the alloy core reacts with silicon diffused from the core, forming a silicon carbonitride interface layer in situ. At the same time, this interface layer is firmly connected to the surrounding carbon skeleton through carbon bonding.
[0065] 12. Cooling and Collection: After the reaction is complete, the reaction gas is turned off, and the mixture is allowed to cool naturally to room temperature under argon protection. The product is then removed, yielding the composite anode material.
[0066] This invention transforms brittle silicon into a silicon-magnesium (Si-Mg) tough alloy phase through alloying. Magnesium not only acts as a conductive additive, but more importantly, the resulting ductile phase can directly absorb and dissipate the localized stress generated by the volume change of the silicon phase during charge and discharge through reversible plastic deformation, significantly reducing the tendency for particle breakage. Simultaneously, the carbon framework is not a simple monopore structure, but a three-tiered pore system with clearly defined functions: mesopores (2-20 nm) ensure rapid lithium-ion transport; macropores (50-300 nm) serve as the main buffer chamber, providing space for alloy core expansion; and finally, macropores (0.5-3 μm) form a mechanically stable framework and promote overall electrolyte wetting. This synergistic design achieves a unity of ion transport, stress buffering, and structural stability. A silicon carbonitride interface layer is grown in situ between the alloy core and the carbon framework via chemical vapor deposition (CVD). The silicon carbonitride interface layer is bonded to the silicon core and the carbon outer layer through strong covalent bonds such as Si-C and Si-NC, forming a strong connection that ensures the continuous stability of the electronic pathway under long-term drastic volume changes and effectively prevents the stripping of active material from the conductive network. This invention also incorporates lithium fluoride (LiF) nanoparticles as a functional component, which are pre-uniformly embedded into the pores or surface of the carbon framework. During battery cycling, the lithium fluoride (LiF) nanoparticles act as a repair agent, undergoing localized decomposition and redeposition at the damaged areas of the solid electrolyte interphase (SEI) film, preferentially repairing weak points. This actively guides the formation and maintenance of a dense, stable, and LiF-rich high-quality SEI film, significantly reducing the continuous consumption of active lithium and electrolyte. Therefore, the alloy core, bonding interface, buffer framework, and repair agent constitute an inseparable composite system in terms of spatial distribution and chemical bonding.
[0067] In the preparation process of this invention: a mixture of alloy core and precursor carbon skeleton is placed in a mixed atmosphere containing carbon and nitrogen sources for a one-time chemical vapor deposition treatment. Within a temperature window of 850-950℃, two objectives are achieved simultaneously: first, further pyrolysis deposition of carbon on the surface of the carbon skeleton to strengthen the skeleton; second, in-situ reaction to generate a silicon carbonitride interface layer on the surface of the alloy core. This process utilizes a single high-temperature process to complete the final shaping and strengthening of the composite structure, simplifying the process. This invention uses a solution impregnation-low-temperature thermal decomposition method to introduce LiF precursors into a porous carbon skeleton. By controlling the precursor concentration, impregnation conditions, and heat treatment temperature, uniform distribution, suitable loading, and good crystallinity of LiF nanoparticles in the carbon skeleton are achieved, ensuring its subsequent function as an effective repair agent. This invention combines the triple physical mechanism of plastic alloy dissipating stress (intrinsic) + multi-level pores accommodating strain (structure) + strong bonding interface maintaining conductivity (interface) with the built-in LiF stable SEI (electrochemical interface) mechanism to form a systematic solution to the root cause of silicon anode failure, thereby simultaneously achieving high capacity, long lifetime, and low expansion.
[0068] It should be noted that the in-situ grown silicon carbonitride interface layer in this invention is an amorphous structure containing silicon, carbon, and nitrogen elements. It is formed in situ by the reaction of methane and ammonia with silicon atoms at high temperature. Due to the different gas source cracking rates at different temperatures, the specific carbon and nitrogen element content ratio will vary with the ratio of carbon and nitrogen sources used and the reaction temperature. As the volume ratio of CH4 to NH3 is 1:5 to 1:1, the carbon content in the interface layer gradually decreases, and the nitrogen content gradually increases. The carbon and nitrogen atoms in this silicon carbonitride interface layer are bonded to the central silicon atom, together forming a stable interface protection network.
[0069] Example 1
[0070] A method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material:
[0071] I. Silicon-Magnesium Alloys (Si x Mg y Preparation of active cores
[0072] 1. Raw material preparation: Weigh high-purity silicon powder (99.9%, particle size ~100 nm) and magnesium powder (99.9%, particle size ~50 μm) according to the target atomic ratio (Si:Mg = 7:3).
[0073] 2. Mechanical alloying: The raw material is placed in the stainless steel tank of a high-energy planetary ball mill and ball-milled for 10 hours at 250 rpm under an argon protective atmosphere, with a ball-to-material ratio of 10:1.
[0074] 3. Heat treatment: The ball-milled powder is heat-treated in a tube furnace at 450°C for 1 hour under an argon atmosphere to promote alloying and release internal stress.
[0075] 4. Sieving: The obtained alloy powder is sieved using a 400-mesh sieve to obtain Si with uniform particle size distribution. x Mg y Alloy core precursor;
[0076] II. Preparation of hierarchical porous carbon framework and embedding of LiF nanoparticles
[0077] 5. Template preparation: Silica nanospheres (2 nm), polymethyl methacrylate (PMMA) microspheres (30 nm) and polystyrene (PS) microspheres (0.5 μm) were mixed at a mass ratio of 1:2:1, dispersed in ethanol, and ultrasonically formed a uniform template suspension.
[0078] 6. Carbon precursor impregnation: The above template suspension and phenolic resin ethanol solution (concentration 10 wt%) are mixed at a volume ratio of 1:2 and stirred for 8 hours to allow the phenolic resin to fully fill the template gaps, thus obtaining a carbon precursor-template composite suspension.
[0079] 7. Pre-curing and carbonization: Evaporate the solvent and pre-cur the mixture at 80°C, and then carbonize it in a tube furnace under an argon atmosphere by heating to 700°C at 2°C / min and holding for 1 hour.
[0080] 8. Template removal and hole creation: The carbonized block is immersed in a 10% hydrofluoric acid (HF) solution for 24 hours to remove the template. The template was then removed by Soxhlet extraction with toluene for 48 hours to obtain a hierarchical porous carbon framework with mesopores, macropores and macropores.
[0081] 9. Introduction of LiF nanoparticles: A hierarchical porous carbon framework was immersed in a mixed ethanol solution of lithium nitrate (LiNO3) and ammonium fluoride (NH4F) (both concentrations 0.05 mol / L) and ultrasonically assisted impregnation for 2 hours. Subsequently, it was dried in a vacuum oven at 60°C and then heat-treated at 200°C for 0.5 hours under an argon atmosphere. and The reaction generates LiF nanoparticles which are then embedded in situ into the pores of the carbon framework.
[0082] III. Construction of Composite Structures and In-situ Growth of Silicon Carbonitride Interface Layer
[0083] 10. Preparation of composite precursor: The Si obtained in step one... x Mg yThe alloy core and the hierarchical porous carbon framework powder loaded with LiF obtained in step two were mechanically mixed at a mass ratio of 1:2 (active material: carbon framework);
[0084] 11. Chemical Vapor Deposition (CVD) Growth of the Interface Layer: The mixed powder was spread evenly in a quartz boat and placed in the isothermal zone of a tube furnace. Under argon carrier gas, the temperature was increased to 850°C at 5°C / min. Subsequently, a mixed gas of methane (CH4, carbon source) and ammonia (NH3, nitrogen source) (CH4:NH3 = 1:1, volume ratio) was introduced at a flow rate of 50 sccm, and the reaction was carried out for 1 hour. CH4 and NH3 decomposed at high temperature and formed on Si... x Mg y The surface of the alloy core reacts with silicon diffused from the core, forming a silicon carbonitride interface layer in situ. At the same time, this interface layer is firmly connected to the surrounding carbon skeleton through carbon bonding.
[0085] 12. Cooling and Collection: After the reaction is complete, the reaction gas is turned off, and the mixture is allowed to cool naturally to room temperature under argon protection. The product is then removed, yielding the composite anode material.
[0086] Example 2
[0087] A method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material:
[0088] I. Silicon-Magnesium Alloys (Si x Mg y Preparation of active cores
[0089] 1. Raw material preparation: Weigh high-purity silicon powder (99.9%, particle size ~100 nm) and magnesium powder (99.9%, particle size ~50 μm) according to the target atomic ratio (Si:Mg = 7:3).
[0090] 2. Mechanical alloying: The raw materials are placed in the stainless steel tank of a high-energy planetary ball mill and ball-milled for 10 hours at 350 rpm under an argon protective atmosphere, with a ball-to-material ratio of 30:1.
[0091] 3. Heat treatment: The ball-milled powder is heat-treated in a tube furnace at 450°C for 4 hours under an argon atmosphere to promote alloying and release internal stress.
[0092] 4. Sieving: The obtained alloy powder is sieved using a 400-mesh sieve to obtain Si with uniform particle size distribution. x Mg y Alloy core precursor;
[0093] II. Preparation of hierarchical porous carbon framework and embedding of LiF nanoparticles
[0094] 5. Template preparation: Silica nanospheres (2 nm), polymethyl methacrylate (PMMA) microspheres (300 nm) and polystyrene (PS) microspheres (5 μm) were mixed at a mass ratio of 1:2:1, dispersed in ethanol, and ultrasonically formed a uniform template suspension.
[0095] 6. Carbon precursor impregnation: The above template suspension is mixed with phenolic resin ethanol solution (concentration 10-30 wt%) at a volume ratio of 1:1 and stirred for 14 hours to allow the phenolic resin to fully fill the template gaps, thus obtaining a carbon precursor-template composite suspension.
[0096] 7. Pre-curing and carbonization: Evaporate the solvent and pre-cur the mixture at 80°C, and then carbonize it in a tube furnace under an argon atmosphere by heating to 700°C at 8°C / min and holding for 3 hours.
[0097] 8. Template removal and hole creation: The carbonized block is immersed in a 10% hydrofluoric acid (HF) solution for 24 hours to remove the template. The template was then removed by Soxhlet extraction with toluene for 48 hours to obtain a hierarchical porous carbon framework with mesopores, macropores and macropores.
[0098] 9. Introduction of LiF nanoparticles: A hierarchical porous carbon framework was immersed in a mixed ethanol solution of lithium nitrate (LiNO3) and ammonium fluoride (NH4F) (both concentrations 0.1 mol / L) and ultrasonically assisted for 2 hours. Subsequently, it was dried in a vacuum oven at 60°C, and then heat-treated at 200°C for 2 hours under an argon atmosphere to allow LiNO3 and NH4F to react and generate LiF nanoparticles, which were then in situ embedded in the pores of the carbon framework.
[0099] III. Construction of Composite Structures and In-situ Growth of Silicon Carbonitride Interface Layer
[0100] 10. Preparation of composite precursor: The Si obtained in step one... x Mg y The alloy core and the hierarchical porous carbon framework powder loaded with LiF obtained in step two were mechanically mixed at a mass ratio of 1:2 (active material: carbon framework);
[0101] 11. Chemical Vapor Deposition (CVD) Growth of the Interface Layer: The mixed powder is spread evenly in a quartz boat and placed in the isothermal zone of a tube furnace. Under argon carrier gas, the temperature is increased to 950°C at a rate of 10°C / min. Subsequently, a mixture of methane (CH4, carbon source) and ammonia (NH3, nitrogen source) is introduced. At a flow rate of 200 sccm, the reaction was carried out for 4 hours. CH4 and NH3 were decomposed at high temperature and reacted in Si. x Mg yThe surface of the alloy core reacts with silicon diffused from the core, forming a silicon carbonitride interface layer in situ. At the same time, this interface layer is firmly connected to the surrounding carbon skeleton through carbon bonding.
[0102] 12. Cooling and Collection: After the reaction is complete, the reaction gas is turned off, and the mixture is allowed to cool naturally to room temperature under argon protection. The product is then removed, yielding the composite anode material.
[0103] Example 3
[0104] A method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material:
[0105] I. Silicon-Magnesium Alloys (Si x Mg y Preparation of active cores
[0106] 1. Raw material preparation: Weigh high-purity silicon powder (99.9%, particle size ~100 nm) and magnesium powder (99.9%, particle size ~50 μm) according to the target atomic ratio (e.g., Si:Mg = 7:3).
[0107] 2. Mechanical alloying: The raw materials are placed in the stainless steel tank of a high-energy planetary ball mill and ball-milled for 20 hours at 300 rpm under an argon protective atmosphere, with a ball-to-material ratio of 20:1.
[0108] 3. Heat treatment: The ball-milled powder is heat-treated in a tube furnace at 500°C for 2 hours under an argon atmosphere to promote alloying and release internal stress.
[0109] 4. Sieving: The obtained alloy powder is sieved using a 400-mesh sieve to obtain Si with uniform particle size distribution. x Mg y Alloy core precursor;
[0110] II. Preparation of hierarchical porous carbon framework and embedding of LiF nanoparticles
[0111] 5. Template preparation: Silica nanospheres (~20 nm), polymethyl methacrylate (PMMA) microspheres (~200 nm) and polystyrene (PS) microspheres (~1 μm) were mixed at a mass ratio of 1:2:1, dispersed in ethanol, and ultrasonically formed a uniform template suspension.
[0112] 6. Carbon precursor impregnation: The above template suspension and phenolic resin ethanol solution (concentration 20 wt%) are mixed at a volume ratio of 1:1 and stirred for 12 hours to allow the phenolic resin to fully fill the template gaps, thus obtaining a carbon precursor-template composite suspension.
[0113] 7. Pre-curing and carbonization: Evaporate the solvent and pre-cur the mixture at 80°C, and then carbonize it in a tube furnace under an argon atmosphere by heating to 800°C at 5°C / min and holding for 2 hours.
[0114] 8. Template removal and hole creation: The carbonized block is immersed in a 10% hydrofluoric acid (HF) solution for 24 hours to remove the template. The template was then removed by Soxhlet extraction with toluene for 48 hours to obtain a hierarchical porous carbon framework with mesopores, macropores and macropores.
[0115] 9. Introduction of LiF nanoparticles: A hierarchical porous carbon framework was immersed in a mixed ethanol solution of lithium nitrate (LiNO3) and ammonium fluoride (NH4F) (both concentrations 0.1 mol / L) and ultrasonically assisted for 2 hours. Subsequently, it was dried in a vacuum oven at 60°C, and then heat-treated at 300°C for 1 hour under an argon atmosphere to allow LiNO3 and NH4F to react and generate LiF nanoparticles, which were then in situ embedded in the pores of the carbon framework.
[0116] III. Construction of Composite Structures and In-situ Growth of Silicon Carbonitride Interface Layer
[0117] 10. Preparation of composite precursor: The Si obtained in step one... x Mg y The alloy core and the hierarchical porous carbon framework powder loaded with LiF obtained in step two were mechanically mixed at a mass ratio of 1:4 (active material: carbon framework);
[0118] 11. Chemical Vapor Deposition (CVD) Growth of the Interface Layer: The mixed powder was spread evenly in a quartz boat and placed in the isothermal zone of a tube furnace. Under argon carrier gas, the temperature was increased to 900°C at 10°C / min. Subsequently, a mixed gas of methane (CH4, carbon source) and ammonia (NH3, nitrogen source) (CH4:NH3 = 1:3, volume ratio) was introduced at a flow rate of 100 sccm, and the reaction was carried out for 2 hours. CH4 and NH3 decomposed at high temperature and formed on Si... x Mg y The surface of the alloy core reacts with silicon diffused from the core, forming a silicon carbonitride interface layer in situ. At the same time, this interface layer is firmly connected to the surrounding carbon skeleton through carbon bonding.
[0119] 12. Cooling and Collection: After the reaction is complete, the reaction gas is turned off, and the mixture is allowed to cool naturally to room temperature under argon protection. The product is then removed, yielding the composite anode material.
[0120] Example 4
[0121] A method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material:
[0122] I. Silicon-Magnesium Alloys (Si x Mg y Preparation of active cores
[0123] 1. Raw material preparation: Weigh high-purity silicon powder (99.9%, particle size ~100 nm) and magnesium powder (99.9%, particle size ~50 μm) according to the target atomic ratio (e.g., Si:Mg = 7:3).
[0124] 2. Mechanical alloying: The raw materials are placed in the stainless steel tank of a high-energy planetary ball mill and ball-milled for 20 hours at 300 rpm under an argon protective atmosphere, with a ball-to-material ratio of 30:1.
[0125] 3. Heat treatment: The ball-milled powder is heat-treated in a tube furnace at 500°C for 2 hours under an argon atmosphere to promote alloying and release internal stress.
[0126] 4. Sieving: The obtained alloy powder is sieved using a 400-mesh sieve to obtain Si with uniform particle size distribution. x Mg y Alloy core precursor;
[0127] II. Preparation of hierarchical porous carbon framework and embedding of LiF nanoparticles
[0128] 5. Template preparation: Silica nanospheres (10 nm), polymethyl methacrylate (PMMA) microspheres (200 nm) and polystyrene (PS) microspheres (2 μm) were mixed at a mass ratio of 1:2:1, dispersed in ethanol, and ultrasonically formed a uniform template suspension.
[0129] 6. Carbon precursor impregnation: Mix the above template suspension with phenolic resin ethanol solution (concentration 10-30 wt%) at a volume ratio of 1:1 and stir for 12 hours to allow the phenolic resin to fully fill the template gaps, thus obtaining a carbon precursor-template composite suspension.
[0130] 7. Pre-curing and carbonization: Evaporate the solvent and pre-cur the mixture at 80°C, and then carbonize it in a tube furnace under an argon atmosphere by heating to 900°C at 8°C / min and holding for 3 hours.
[0131] 8. Template removal and pore formation: The carbonized bulk material is immersed in 10% hydrofluoric acid (HF) solution for 24 hours to remove the SiO2 template, and then extracted with toluene Soxhlet for 48 hours to remove PMMA and PS templates, resulting in a hierarchical porous carbon framework with mesopores, macropores and macropores.
[0132] 9. Introduction of LiF nanoparticles: A hierarchical porous carbon framework was immersed in a mixed ethanol solution of lithium nitrate (LiNO3) and ammonium fluoride (NH4F) (both concentrations 0.2 mol / L) and ultrasonically assisted for 2 hours. Subsequently, it was dried in a vacuum oven at 60°C, and then heat-treated at 400°C for 2 hours under an argon atmosphere to allow LiNO3 and NH4F to react and generate LiF nanoparticles, which were then in situ embedded in the pores of the carbon framework.
[0133] III. Construction of Composite Structures and In-situ Growth of Silicon Carbonitride Interface Layer
[0134] 10. Preparation of composite precursor: The Si obtained in step one... x Mg y The alloy core and the hierarchical porous carbon framework powder loaded with LiF obtained in step two were mechanically mixed at a mass ratio of 1:4 (active material: carbon framework);
[0135] 11. Chemical Vapor Deposition (CVD) Growth of the Interface Layer: The mixed powder was spread evenly in a quartz boat and placed in the isothermal zone of a tube furnace. Under argon carrier gas, the temperature was increased to 900°C at 10°C / min. Subsequently, a mixed gas of methane (CH4, carbon source) and ammonia (NH3, nitrogen source) (CH4:NH3 = 1:2, volume ratio) was introduced at a flow rate of 150 sccm, and the reaction was carried out for 4 hours. CH4 and NH3 decomposed at high temperature and formed on Si... x Mg y The surface of the alloy core reacts with silicon diffused from the core, forming a silicon carbonitride interface layer in situ. At the same time, this interface layer is firmly connected to the surrounding carbon skeleton through carbon bonding.
[0136] 12. Cooling and Collection: After the reaction is complete, the reaction gas is turned off, and the mixture is allowed to cool naturally to room temperature under argon protection. The product is then removed, yielding the composite anode material.
[0137] Example 5
[0138] A method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material:
[0139] I. Silicon-Magnesium Alloys (Si x Mg y Preparation of active cores
[0140] 1. Raw material preparation: Weigh high-purity silicon powder (99.9%, particle size ~100 nm) and magnesium powder (99.9%, particle size ~50 μm) according to the target atomic ratio (e.g., Si:Mg = 7:3).
[0141] 2. Mechanical alloying: The raw materials are placed in the stainless steel tank of a high-energy planetary ball mill and ball-milled for 30 hours at 350 rpm under an argon protective atmosphere, with a ball-to-material ratio of 30:1.
[0142] 3. Heat treatment: The ball-milled powder is heat-treated in a tube furnace at 600°C for 4 hours under an argon atmosphere to promote alloying and release internal stress.
[0143] 4. Sieving: The obtained alloy powder is sieved using a 400-mesh sieve to obtain Si with uniform particle size distribution. x Mg y Alloy core precursor;
[0144] II. Preparation of hierarchical porous carbon framework and embedding of LiF nanoparticles
[0145] 5. Template preparation: Silica nanospheres (20 nm), polymethyl methacrylate (PMMA) microspheres (300 nm) and polystyrene (PS) microspheres (5 μm) were mixed at a mass ratio of 1:2:1, dispersed in ethanol, and ultrasonically formed a uniform template suspension.
[0146] 6. Carbon precursor impregnation: The above template suspension and phenolic resin ethanol solution (concentration 30 wt%) are mixed at a volume ratio of 2:1 and stirred for 14 hours to allow the phenolic resin to fully fill the template gaps, thus obtaining a carbon precursor-template composite suspension.
[0147] 7. Pre-curing and carbonization: Evaporate the solvent and pre-cur the mixture at 80°C, and then carbonize it in a tube furnace under an argon atmosphere by heating to 900°C at 10°C / min and holding for 3 hours.
[0148] 8. Template removal and hole creation: The carbonized block is immersed in a 10% hydrofluoric acid (HF) solution for 24 hours to remove the template. The template was then removed by Soxhlet extraction with toluene for 48 hours to obtain a hierarchical porous carbon framework with mesopores, macropores and macropores.
[0149] 9. Introduction of LiF nanoparticles: A hierarchical porous carbon framework was immersed in a mixed ethanol solution of lithium nitrate (LiNO3) and ammonium fluoride (NH4F) (both concentrations 0.5 mol / L) and ultrasonically assisted for 2 hours. Subsequently, it was dried in a vacuum oven at 60°C, and then heat-treated at 400°C for 2 hours under an argon atmosphere to allow LiNO3 and NH4F to react and generate LiF nanoparticles, which were then in situ embedded in the pores of the carbon framework.
[0150] III. Construction of Composite Structures and In-situ Growth of Silicon Carbonitride Interface Layer
[0151] 10. Preparation of composite precursor: The Si obtained in step one...x Mg y The alloy core and the hierarchical porous carbon framework powder loaded with LiF obtained in step two were mechanically mixed at a mass ratio of 1:5 (active material: carbon framework);
[0152] 11. Chemical Vapor Deposition (CVD) Growth of the Interface Layer: The mixed powder is spread evenly in a quartz boat and placed in the isothermal zone of a tube furnace. Under argon carrier gas, the temperature is increased to 950°C at a rate of 15°C / min. Subsequently, a mixture of methane (CH4, carbon source) and ammonia (NH3, nitrogen source) is introduced. The flow rate was 200 sccm, and the reaction was carried out for 4 hours under these conditions. CH4 and NH3 were decomposed at high temperature and reacted in Si. x Mg y The surface of the alloy core reacts with silicon diffused from the core, forming a silicon carbonitride interface layer in situ. At the same time, this interface layer is firmly connected to the surrounding carbon skeleton through carbon bonding.
[0153] 12. Cooling and Collection: After the reaction is complete, the reaction gas is turned off, and the mixture is allowed to cool naturally to room temperature under argon protection. The product is then removed, yielding the composite anode material.
[0154] Comparative Example 1: Pure nano-silicon / hierarchical porous carbon (no Mg, no silicon carbonitride layer, no LiF)
[0155] 1. Raw material preparation: High-purity nano-silicon powder (99.9%, particle size ~100 nm) is used directly as the active material.
[0156] 2. Preparation of hierarchical porous carbon framework: Prepare pure hierarchical porous carbon framework without LiF by following the methods in steps 5 to 8 of the patent embodiment (i.e., skip the LiF introduction process in step 9).
[0157] 3. Simple mechanical mixing: The above-mentioned nano-silicon powder and the prepared hierarchical porous carbon skeleton powder are mechanically mixed at a mass ratio of 1:4 (silicon: carbon skeleton) (e.g., ball milling for 2 hours in an argon-protected glove box).
[0158] 4. Material Collection: After uniform mixing, the resulting powder is pure nano-silicon / hierarchical porous carbon composite anode material. No chemical vapor deposition treatment is performed.
[0159] Comparative Example 2: Si 0.7 Mg 0.3 Hierarchical porous carbon (with alloying, no silicon carbonitride interface layer, no LiF)
[0160] 1. Si x Mg y Alloy core preparation: Si was prepared entirely according to steps 1 to 4 of the patent embodiment. 0.7 Mg0.3 Alloy core.
[0161] 2. Preparation of hierarchical porous carbon framework: Prepare pure hierarchical porous carbon framework without LiF by following the methods in steps 5 to 8 of the patent embodiment (i.e., skip the LiF introduction process in step 9).
[0162] 3. Simple mechanical mixing: The Si obtained in step 1 is mixed... 0.7 Mg 0.3 The alloy core and the graded porous carbon framework powder obtained in step 2 are mechanically mixed at a mass ratio of 1:4 (e.g., ball milling for 2 hours in an argon-protected glove box).
[0163] 4. Material collection: After thorough mixing, the resulting powder is Si. 0.7 Mg 0.3 Hierarchical porous carbon composite anode material. No chemical vapor deposition (CVD) treatment is performed.
[0164] Comparative Example 3:
[0165] Commercial nano-silicon-carbon composite material (silicon content ~15%) is used.
[0166] Material post-processing and electrode fabrication:
[0167] Grinding and sieving: The final composite material is lightly ground in an agate mortar and passed through a 400-mesh sieve to obtain a uniform electrode active material powder.
[0168] Electrode preparation: The negative electrode active material, conductive agent (Super P), and binder (polyvinylidene fluoride, PVDF) were mixed in N-methylpyrrolidone (NMP) solvent at a mass ratio of 8:1:1 and ground into a uniform slurry. The slurry was coated onto copper foil and dried in a vacuum oven at 120°C for 12 hours. Subsequently, it was compacted using a roller mill and punched into circular pieces with a diameter of 12 mm to serve as the working electrode.
[0169] Battery assembly: In an argon-protected glove box, lithium metal sheets were used as the counter and reference electrodes, and Celgard 2400 was used as the separator. A solution containing EC / DMC / EMC (volume ratio 1:1:1) and 2% FEC additive was used as the electrolyte to assemble CR2032 coin cells.
[0170] Electrochemical performance testing
[0171] Cyclic performance testing: Using a battery testing system, at a rate of 0.5C (based on theoretical material capacity calculations), at 2.0-0.01 V (vs. Li) + Constant current charge-discharge tests were performed within the / Li voltage window, and the cycle capacity and coulombic efficiency were recorded.
[0172] First coulombic efficiency test: Record the capacity of the first discharge (lithium insertion) and the first charge (lithium removal), and calculate the first coulombic efficiency (first charge capacity / first discharge capacity × 100%).
[0173] Electrode expansion rate test: Use a thickness gauge to measure the thickness of the electrode sheet before cycling and after a certain number of cycles (e.g., 100 cycles), and calculate the thickness expansion rate.
[0174] Patent CN118825269A shows a first-week charging specific capacity of 1753 mAh / g, a first-week coulombic efficiency of 93.1%, a capacity retention rate of 75% at a 1C high rate, and a first-week lithium intercalation expansion rate of 85%. CN118919673A has a capacity of 2110 mAh / g and an initial charge / discharge efficiency of 92.45%; the electrode compaction density is 1.76 g / cm³, and the capacity retention is 88.2% after 600 cycles under 3C / 1C charge / discharge conditions. CN118978160A has a capacity of 2553 mAh / g at 0.2C, and an energy of 5.45 Wh at a 30A ultra-high discharge rate, with a capacity retention of ≥80% after 200 cycles. CN118929633A has an initial charge specific capacity of 1905 mAh / g at 0.1C, an initial coulombic efficiency of 92.7%, and a capacity retention of 91.7% after 50 cycles. CN118825278A has an initial coulombic efficiency of 92.89% and a specific capacity of 1498 mAh / g at 0.8V. After 1000 cycles at 0.5C, the present invention exhibits a capacity retention of 93.0%, a 5C / 0.2C capacity ratio of 92%, an electrode thickness expansion rate of 35%, an initial charge specific capacity of 2646 mAh / g, and an initial coulombic efficiency of 96.2%.
[0175] Table 1. Performance of Examples and Comparative Samples
[0176]
[0177] As shown in Table 1, the electrochemical performance test results indicate that the pure nano-silicon / hierarchical porous carbon material (Comparative Example 1), which is simply physically mixed, exhibits a thickness expansion rate as high as 155% after 100 cycles, indicating that the drastic volume change leads to severe structural damage. After alloying with magnesium (Comparative Example 2), the expansion rate decreased to 120%, confirming that the ductile Si-Mg alloy phase possesses a preliminary stress buffering effect. In Examples 1-3, thanks to the physical buffering provided by the alloy phase, the hierarchical porous framework, and the strong confinement of the silicon carbonitride covalent interface layer, the electrode thickness expansion rate was significantly suppressed to between 35% and 45%, with Example 3 showing the best result at only 35%. This demonstrates that the strong bonding interface of the present invention effectively prevents the peeling and slippage of the active material from the carbon network.
[0178] The first-cycle coulombic efficiency of the conventional silicon-carbon composite materials in Comparative Examples 1 and 3 was generally below 90%, which was attributed to repeated rupture of the SEI film caused by silicon expansion during the initial cycle and excessive electrolyte consumption. Example 3 significantly improved the first-cycle coulombic efficiency to 96.2%, exceeding the current commercial level. This was mainly due to the active guidance of pre-embedded LiF nanoparticles in the channels to form a dense, robust, and self-healing LiF-rich interface during the initial cycle, which greatly reduced irreversible active lithium consumption.
[0179] After 1000 long cycles at 0.5C, the capacity retention rates of the commercial nano-silicon carbon in Comparative Example 3 and the interface-free material in Comparative Example 2 were only 72.0% and 65.3%, respectively, while the embodiment groups of the present invention maintained above 90% (Example 3 reached as high as 93.0%). Furthermore, Example 3 achieved 92% of the capacity utilization at a high 5C rate compared to 0.2C, significantly higher than the 60% of Comparative Example 1 and the 55% of the commercial material. This indicates that the hierarchical porous carbon not only provides ample buffer space, but the rational combination of mesopores and macropores also greatly promotes rapid lithium-ion transport and electrolyte wetting. Combined with the stable electronic pathways provided by the silicon carbonitride interface layer, this achieves a balance between long-term cycling performance and fast-charging performance.
[0180] Comparing Examples 1 to 3, it can be seen that with the optimization of synthesis process parameters (such as synthesis temperature, carbon / silicon ratio, CVD gas ratio, and LiF precursor concentration), various properties show a gradual upward trend. Example 3, at 900℃, CH4:NH3=1:3, and a suitable LiF loading, achieved the optimal balance between interface layer thickness, carbon skeleton strength, and LiF repair mechanism, with all data reaching their optimal state.
[0181] Table 1 above demonstrates that the present invention overcomes the defects of traditional silicon-carbon anode materials caused by silicon volume expansion, such as interface failure, structural pulverization, and continuous thickening of SEI film, through the synergy of intrinsic stress dispersion, multi-level structural buffering, strong covalent bonding, and active interface repair. It is a long-life, low-expansion silicon-based anode material with extremely high commercial application potential.
[0182] Figure 2 The figures show the long-term cycle stability test results of a battery using the sample of this invention as the negative electrode at a 0.5C rate. As can be seen from the figure, the capacity retention of the material exhibits a steady and slow decreasing trend with increasing cycle number. After 1000 cycles, the capacity retention is approximately 93%, indicating that the material possesses excellent cycle life and structural stability.
[0183] Figure 3The first charge-discharge curves of the battery using the sample of this invention as the negative electrode demonstrate the material's excellent lithium storage performance and low initial irreversible capacity loss. The figure shows that the material's initial discharge specific capacity is 2750 mAh / g, and its initial charge specific capacity reaches 2646 mAh / g, corresponding to an initial coulombic efficiency of approximately 96.2%. The curve characteristics indicate that the material exhibits low polarization and good reversibility during charge and discharge.
[0184] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface, characterized in that the method... include: (1) Prepare silicon-magnesium alloy active cores from silicon powder and magnesium powder; (2) Preparation of hierarchical porous carbon framework; (3) Lithium fluoride nanoparticles are embedded in the voids of the hierarchical porous carbon framework to form a hierarchical porous carbon framework carrying lithium fluoride nanoparticles. (4) The silicon-magnesium alloy active core is mechanically mixed with the hierarchical porous carbon framework loaded with lithium fluoride nanoparticles to form a composite precursor. (5) Chemical vapor deposition is performed on the composite precursor to grow a silicon carbonitride interface layer in situ on the surface of the silicon-magnesium alloy active core, thereby forming the composite anode material.
2. The method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface according to claim 1, characterized in that, In step (1), the preparation of silicon powder and magnesium powder into a silicon-magnesium alloy active core includes: Silicon powder and magnesium powder were weighed according to the target atomic ratio, and the silicon powder and magnesium powder were ball-milled under an argon protective atmosphere with a ball-to-material ratio of 10:1 to 30:1 to obtain silicon-magnesium mixed powder. The silicon-magnesium mixed powder is then subjected to heat treatment at 450-600℃ for 1-4 hours to obtain the active core of the silicon-magnesium alloy.
3. The method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface according to claim 1, characterized in that, In step (2), the preparation of the hierarchical porous carbon framework includes: Silica nanospheres, polymethyl methacrylate microspheres and polystyrene microspheres were mixed in a mass ratio of 1:2:1 and dispersed in ethanol to form a uniform template suspension. The template suspension was mixed with the carbon precursor solution and stirred to obtain a carbon precursor-template composite suspension. The carbon precursor-template composite suspension was pre-cured by evaporating solvent at 80°C, and then heated to 700-900°C under argon atmosphere for heat preservation carbonization to obtain the carbonized block. The carbonized block is immersed in hydrofluoric acid solution to remove silica, and then Soxhlet extraction is performed to remove polymethyl methacrylate and polystyrene to obtain the hierarchical porous carbon skeleton.
4. The method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface according to claim 1, characterized in that, In step (3), the embedding of lithium fluoride nanoparticles into the voids of the hierarchical porous carbon framework to form a hierarchical porous carbon framework loaded with lithium fluoride nanoparticles includes: The hierarchical porous carbon framework is immersed in an ethanol solution of lithium nitrate and ammonium fluoride for ultrasonic impregnation, then vacuum dried, and then heat-treated in an argon atmosphere at a temperature of 200~400℃ to generate lithium fluoride nanoparticles, which are then embedded in the pores of the carbon framework to obtain the hierarchical porous carbon framework carrying lithium fluoride nanoparticles.
5. The method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface according to claim 1, characterized in that, In step (5), the chemical vapor deposition of the composite precursor to grow a silicon carbonitride interface layer in situ on the surface of the silicon-magnesium alloy active core, ultimately forming the composite anode material, includes: Under an argon protective atmosphere, the composite precursor is heated to 850~950℃, and then a mixture of methane and ammonia is introduced to react, thereby growing a silicon carbonitride interface layer in situ on the surface of the silicon-magnesium alloy active core. After the reaction is complete, the methane and ammonia gas are turned off, and the mixture is allowed to cool naturally under an argon protective atmosphere to obtain the composite anode material.
6. The method for preparing a silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface according to claim 5, characterized in that, The volume ratio of methane to ammonia is 1:5 to 1:
1.
7. A silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface, characterized in that, The composite anode material comprises: a silicon-magnesium alloy active core, a silicon carbonitride interface layer coated on the surface of the silicon-magnesium alloy active core, a hierarchical porous carbon framework coated outside the interface layer, and lithium fluoride nanoparticles uniformly dispersed in the hierarchical porous carbon framework.
8. The silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface according to claim 7, characterized in that, In the silicon-magnesium alloy active core, the atomic ratio of Si:Mg is 6:4 to 9:
1.
9. A silicon-magnesium / silicon carbonitride / hierarchical porous lithium carbon-fluoride composite anode material with a self-healing interface according to claim 7, characterized in that, The thickness of the silicon carbonitride interface layer is 5-50 nm; The hierarchical porous carbon framework has a hierarchical pore structure of mesopores, macropores and macropores. The mesopores have a diameter of 2-20 nm, the macropores have a diameter of 50-300 nm, and the macropores have a diameter of 0.5-5 μm.
10. A lithium-ion battery, characterized in that, The composite anode material prepared by the preparation method according to any one of claims 1-6, or the composite anode material according to any one of claims 7-9.
Citation Information
Patent Citations
Low-expansion silicon carbon adopting composite porous carbon as well as preparation method and application of low-expansion silicon carbon
CN118825269A
Coated modified silicon carbon negative electrode material as well as preparation method and application thereof
CN118825278A
Silicon-carbon negative electrode material and preparation method and application thereof
CN118919673A
Silicon-carbon composite material with silicon-carbon alternate multi-level structure and preparation method and application thereof
CN118929633A
Silicon-carbon negative electrode material and preparation method and application thereof
CN118978160A